ANALISIS IMPLEMENTASI PERATURAN MENTERI KEUANGAN N0.158/PERATURAN MENTERI KEUANGAN NO.04/2017 TENTANG PENGGUNAAN APLIKASI MANIFES BEA CUKAI PADA PROSES PENERBITAN DOKUMEN INWARD & DOKUMEN OUTWARD (STUDI KASUS PT. XYZ LOGISTICS INDONESIA) - Ajahlia, Yusniar Jannahti; Nahshir, Achsanul (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This study is shown to analyze the procedure for implementing the regulation of the Minister of Finance No. 158 / Regulation of the Minister of Finance No. 04 of 2017 concerning the process of issuing inward manifest and outward manifest documents at PT. XYZ Logistics. In the process of issuing manifest documents, problems often arise that can hinder the unloading or transportation of goods. These problems can occur due to errors in data entry, causing the documents to be redressed by customs, manifest documents that are not retrieved for data reconciliation, and delays in the submission of manifest documents. This research is qualitative with a descriptive approach. The determination of informants is based on employees who handle the issuance of manifest documents directly, informants from customs institutions, and academic informants chosen based on the export-import courses they teach. The results of the study related to the analysis of the implementation of PMK No. 158 PMK No.04 of 2017 concerning the procedures for issuing manifest documents. This study shows that PT. XYZ Logistics understands the policy in PMK No. 158 PMK No. 4 of 2017 and comprehends the process of issuing manifest documents. However, in practice, there are still frequent errors that cause delays in the submission of manifest documents. This study aims to identify the impact of errors in the process of issuing manifest documents and how PT. XYZ Logistics addresses the problems that arise in the process of issuing manifest documents in accordance with PMK No. 158 PMK No. 04 of 2017. Suggestions that can be proposed include increasing awareness of the responsibilities given, enhancing human resources as export-import regulations or policies can change, and fostering cooperation among employees in carrying out their duties.